"Who cares" is key: factors associated with oral health status in children living with HIV in Phnom Penh, Cambodia. Issue 4 (2nd April 2020) - Kikuchi, Kimiyo; Furukawa, Yusuke; Tout, Sovannary; Pal, Khuondyla; Huot, Chantheany; Yi, Siyan
ABSTRACT: This cross-sectional study aimed to identify social, clinical, and behavioral factors associated with the oral health status of children living with HIV in Phnom Penh, focusing particularly on the effect of primary caregiver type. Data were collected through separate interviews with children and caregivers. The decayed, missing, filled permanent teeth (DMFT) index and debris index scores were assessed for each child. Associations between oral health status and caregiver type as well as with other factors were examined using multiple linear regression. Of 142 total dyads (mean child and caregiver age, 12.3 (SD 1.8) and 44.8 (SD 10.6) years, respectively) 48.6% and 29.6% of caregivers were biological parents and institutional staff, respectively. Children with institutional staff as a primary caregiver had a lower DMFT score (2.81 vs. 5.50), higher rate of ever visiting a dentist (90.5% vs. 50.7%), and better oral health status than those cared for by biological parents. Higher DMFT score was negatively associated with institutional staff as primary caregiver (β: −1.642, 95% CI: −2.925, −0.360) and positively associated with longer antiretroviral therapy period (β: 0.223, 95% CI: 0.056, 0.390). Targeted oral health care programs are needed for children living with HIV whose biological parents are their primary caregivers.